PENGEMBANGAN PERMAINAN PESAN BERANTAI UNTUK KONSENTRASI ANAK DI KELOMPOK A TK KARTIKA II-1 PALEMBANG - Fricilia Febriani; Syafdaningsih syafar; Rukiyah Rukiyah (FKIP Universitas sriwijaya, 2019)
This study is entitled Development of a Chain Message Game for Children Concentration of A TK Kartika II-1 Palembang Group which aims to produce chain message games that meet valid and practical criteria. This type of research is Research Development and was developed using a combination of the Rowntree development model and Tessmer evaluation. The Rowntree development model consists of three stages, namely the planning, development, and evaluation stages. In the evaluation phase consists of four stages, namely the stages of self evaluation, expert review, one to one evaluation, and small group evaluation. In the expert review stage using material experts and media experts. The technique of collecting data uses a walkthrough with a sheet of material and media expert validation test instruments and observation with an observation sheet instrument. The results showed that the validity of the material was 87 with a very valid category. The results also showed that the validity of the media was 92 with very valid categories. From the results of material validation and media validation, the product has a validity value of 89 with a very valid category. In the stage of one to one evaluation involving three children, the score was 92% with a very practical category. In the small group evaluation phase involving nine children the score was 93% with a very practical category because it met the practicality criteria. From all the steps that have been done, it can be concluded that the chain message game for the concentration of group A children is declared valid and practical.